Evidence for an Incipient Decline in Numbers of Missing Girls in China and India - Das Gupta, Monica (2012)
The apparently inexorable rise in the proportion of "missing girls" in much of East and South Asia has attracted much attention among researchers and policymakers. An encouraging trend was suggested by the case of South Korea, where child sex ratios (males to females under age 5) were the highest in Asia but peaked in the mid-1990s and normalized thereafter. Using census data, we examine whether similar trends have begun to manifest themselves in the two most populous countries of this region, China and India. The data indicate that child sex ratios are peaking in these countries, and in many subnational regions are beginning to trend toward lower, more normal values. This suggests that, with continuing economic and social development and vigorous public policy efforts to reduce son preference, the "missing girls" phenomenon could eventually disappear in Asia.